2011
DOI: 10.5694/j.1326-5377.2011.tb03266.x
|View full text |Cite
|
Sign up to set email alerts
|

Major depression among methamphetamine users entering drug treatment programs

Abstract: Objective: To determine the prevalence of major depression among people entering treatment for methamphetamine use. Design, setting and participants: The study was a cross-sectional survey involving 41 specialised drug and alcohol treatment agencies in Brisbane and Sydney. Services provided by these agencies included residential rehabilitation, detoxification and counselling. Participants were 400 people entering treatment for methamphetamine use who were recruited from participating treatment agencies between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 16 publications
3
43
0
Order By: Relevance
“…In a number of studies, rates of depression among methamphetamine users are consistently documented as greater than 35% (Dyer & Cruickshank, 2005; Kay-Lambkin, Baker, Lee, Jenner, & Lewin, 2011; McKetin, Lubman, Lee, Ross, & Slade, 2011; Sutcliffe et al, 2009). In contrast, according to a survey conducted by the Centers for Disease Control and Prevention (CDC), general population rates for current depression are 9.0%, including 3.4% for major depressive disorder (Centers for Disease Control and Prevention, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of studies, rates of depression among methamphetamine users are consistently documented as greater than 35% (Dyer & Cruickshank, 2005; Kay-Lambkin, Baker, Lee, Jenner, & Lewin, 2011; McKetin, Lubman, Lee, Ross, & Slade, 2011; Sutcliffe et al, 2009). In contrast, according to a survey conducted by the Centers for Disease Control and Prevention (CDC), general population rates for current depression are 9.0%, including 3.4% for major depressive disorder (Centers for Disease Control and Prevention, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of methamphetamine use and depression is likely bidirectional, with methamphetamine use contributing to changes in mood and being used as a self-medicating behavior to reduce symptoms of depression (McKetin et al, 2011; Semple, Zians, Strathdee, & Patterson, 2007). Multiple lines of evidence, such as cerebral vascular accidents (Perez, Arsura, & Strategos, 1999; Ohta, Mori, Yoritaka, Okamoto, & Kishida, 2005) as well as anatomic changes like left ventricular dilation (Lord, Shenouda, Mcllwain, Charalampidis, Lucchesi, & Varner, 2010), suggest that neurotoxicity occurs as a consequence of chronic methamphetamine exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Both acute and chronic MA abuses have serious medical, psychiatric, and dental repercussions. Short- and long-term health effects of MA abuse include stroke (Perez, Arsura, & Strategos, 1999), cardiac arrhythmia (Haning & Goebert, 2007), depression (McKetin, Lubman, Lee, Ross, & Slade, 2011; Thomas, Angoa Perez, Francescutti-Verbeem, Shah, & Kuhn, 2010), anxiety (Glasner-Edwards et al, 2010), insomnia, paranoia (McGregor et al, 2005), and structural and chemical changes to the brain (Sekine et al, 2003; Yoon et al, 2010). Depression, in particular, is a public health concern because cost-of-illness research has indicated that depression is associated with considerable economic burden, with most of the burden deriving from lost work productivity (Wang, Simon, & Kessler, 2003).…”
mentioning
confidence: 99%
“…It is not uncommon for depression and substance use to co-occur (McKetin et al, 2011; Thomas et al, 2010). The association between the two conditions is likely bidirectional, with short- and long-term substance use resulting in mood changes and substance use being a compensatory behavior to alleviate symptoms of depression (Koob et al, 2014).…”
mentioning
confidence: 99%
“…The interplay between psychoactive substance use and mental illnesses has been documented by numerous studies (McKetin et al, 2011; Wang et al, 2012). In particular, psychoactive substances have direct effect on monoamine regulation within the brain, producing various depressive symptoms including low mood, fatigue, sleeping disorder, appetite changes, irritability, and/or poor concentration (Bamford et al, 2008; London et al, 2004).…”
Section: Discussionmentioning
confidence: 99%